High-stable standard samples of mass in the nano-gram range - Mikhailov, I.F.; Baturin, A.A.; Bugaev, Ye.A.; Mikhailov, A.I.; Borisova, S.S. (Functional Materials, 2013)
High-stable mass standards prepared as magnetron sputtered super-smooth metal layers deposited on single crystal substrates were attested. The thin film standards were found to meet the requirements to government standards: they are homogeneous, long-lived, and can be attested by several independent methods. Using the standards, the measurement accuracy is provided not worse than 1 ng in the range from 1 to 17 ng, and not worse than 8 ng in the range from 17 to 3800 ng.